2006
DOI: 10.1038/sj.jcbfm.9600177
|View full text |Cite
|
Sign up to set email alerts
|

Global Cerebral Blood Flow and Metabolism during Acute Hyperketonemia in the Awake and Anesthetized Rat

Abstract: In the human setting, it has been shown that acute increase in the concentration of ketone bodies by infusion of b-hydroxybutyrate increased the cerebral blood flow (CBF) without affecting the overall cerebral metabolic activity. The mechanism by which this effect of ketone bodies was mediated is not known. Alterations in several parameters may possibly explain the increase in CBF and the resetting of the relation between CBF and cerebral metabolism. To study this phenomenon further, we measured global CBF and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 42 publications
3
11
2
Order By: Relevance
“…Our results demonstrate that ketosis (induced by a ketogenic diet) reduces CBF and decreases brain levels of high-energy phosphates, which would appear to suggest adverse consequences. In apparent contrast, a study of ketone infusion in adult rats found an increase in CBF—a finding one might not predict from our results (40). The reason for the variation in results between those data and our data is unclear.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results demonstrate that ketosis (induced by a ketogenic diet) reduces CBF and decreases brain levels of high-energy phosphates, which would appear to suggest adverse consequences. In apparent contrast, a study of ketone infusion in adult rats found an increase in CBF—a finding one might not predict from our results (40). The reason for the variation in results between those data and our data is unclear.…”
Section: Discussioncontrasting
confidence: 99%
“…This observation is consistent with previous studies of rats showing that brain oxygen consumption (which is proportional to TCA cycle activity) is unaffected by hyperketonemia whether by acute BHB infusion (Linde et al, 2006) or by starvation for 48 to 72 hours (Dahlquist and Persson, 1976;Hawkins, 1971). …”
Section: Effects Of Hyperketonemia On Glucose Utilization In the Ceresupporting
confidence: 92%
“…In an early study of brain slices/ minces, Openshaw and Bortz (1968) reported that ketone body elevation decreased glucose oxidation, whereas others reported increased lactate formation with no change in glucose oxidation (Ito and Quastel, 1970;Rolleston and Newsholme, 1967). Studies reporting brain glucose utilization by arterio/venous difference (Linde et al, 2006) or 14 C-2-deoxyglucose phosphorylation (Corddry et al, 1982;Crane et al, 1985) in rats during hyperketonemia, whether induced by fasting (2 to 3 days) or by acute BHB infusion, consistently show no change in CMR glc compared with the fed condition, unless fasting is more prolonged when a decrease in CMR glc occurs (Crane et al, 1985). The findings that increased oxidation of ketone bodies occurs without altering either glucose or oxygen consumption suggest that glucose metabolism during hyperketonemia is diverted to lactate production and efflux to the blood, which may occur transiently, as reported by Hawkins et al (1971).…”
Section: Effects Of Hyperketonemia On Glucose Utilization In the Cerementioning
confidence: 97%
“…Rats given an acute infusion of sodium OHB resulting in circulating ketone levels of 6 mmol/L have unchanged CMRglc [50], suggesting that the effect on brain glucose metabolism is indeed different with sudden versus sustained hyperketonemia. Whether this is also the case in humans subjected to a ketone infusion under euglycemia remains to be investigated.…”
Section: Interplay Between Brain Glucose and Ketone Metabolismmentioning
confidence: 97%
“…The latter are generally performed under general anesthesia with isoflurane or halothane, which likely have an effect on brain energy metabolism. One study [50] assessed both anesthetized and awake rats before and after intravenous infusion of sodium betahydroxybutyrate, and found that while none of the groups showed increased CMRglc or CMRO2 at hyperketonemia, global cerebral blood flow (CBF) increased at hyperketonemia by different amounts depending on the anesthetic used (greater increase with halothane compared to pentobarbital), as well as lower CBF and CMRO2 at baseline in rats anesthetized with pentobarbital compared to non-anesthetized rats. The different effects of particular anesthetic compounds on brain metabolism, and potentially different effects on the cerebral response to hyperketonemia, should be taken into account when comparing rat studies with differing methodologies.…”
Section: Brain Ketone Metabolismmentioning
confidence: 97%